Systematic review of the methods used in economic evaluations of targeted physical activity and sedentary behaviour interventions. (July 2019) - Cochrane, M.; Watson, P.M.; Timpson, H.; Haycox, A.; Collins, B.; Jones, L.; Martin, A.; Graves, L.E.F.
Abstract: The burden of noncommunicable diseases (NCD) on health systems worldwide is substantial. Physical inactivity and sedentary behaviour are major risk factors for NCD. Previous attempts to understand the value for money of preventative interventions targeting physically inactive individuals have proved to be challenging due to key methodological challenges associated with the conduct of economic evaluations in public health. A systematic review was carried out across six databases (Medline, SPORTSDiscus, EconLit, PsychINFO, NHS EED, HTA) along with supplementary searches. The review examines how economic evaluations published between 2009-March 2017 have addressed methodological challenges with the aim of bringing to light examples of good practice for future studies. Fifteen economic evaluations from four high-income countries were retrieved; there is a dearth of studies targeting sedentary behaviour as an independent risk factor from physical activity. Comparability of studies from the healthcare and societal perspectives were limited due to analysts' choice in cost categories, valuation technique and time horizon differing substantially. The scarcity of and inconsistencies across economic evaluations for these two behaviours have exposed a mismatch between calls for more preventative action to tackle NCD and the lack of information available on how resources may be optimally allocated in practice. Consequently, this paper offers a table of recommendations on how future studies can be improved. Highlights: Two thirds of studies are not providing evidence for longer term decision-making. Physical activity interventions continue to risk not being appropriately prioritised for investment. Few countries evaluate physical inactivity interventions in the context of scarce resources. Cost categories selected are inconsistent across the healthcare and societal perspectives. Subgroup analysis is the most common approach to incorporating equity.